Presenting the Absent: Representation of Maternal Memory, Embodiment, and Motherhood in My Art - Singh, Ruchika Wason (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
My paper discusses my drawings, paintings, and installations from the first decade of the 2000s, which have grown out of my experience of motherhood as a daughter, being pregnant, and mothering in the postnatal phase. The paper focuses on representation of these experiences in my art making, with specific reference to the nonfigurative expression of my works—that is to say, maternal mothered bodies, including mine, my mother’s, as well as my daughter’s, are absent in my emotive expression.